Spiritual Dimensions of Moral Injury: Contributions of Mental Health Chaplains in the Canadian Armed Forces - Smith-MacDonald, Lorraine A.; Morin, Jean-Sébastien; Brémault-Phillips, Suzette (Frontiers in Psychiatry, 2018)
Moral Injury (MI) describes the profound distress experienced by military personnel as a result of a violation of personal beliefs. Impacting not only psychological, but spiritual, health and well-being, MI is associated with spiritual/religious (S/R) suffering and a need to find hope, trust, connection, reconciliation, and wholeness. Addressing spiritual wounds can help military personnel overcome fundamental barriers that may impede them from effectively engaging in or benefitting from traditional trauma therapies and having a more complete recovery. Military Chaplains in the Canadian Armed Forces (CAF) are both embedded with the troops in garrison and theatre and work closely with service providers such as the Royal Canadian Medical Services. In their role, they offer front-line support and services to members and their families and facilitate access to care. Specific to the assessment and treatment of MI, Mental Health Chaplains (MHCs) offer S/R expertise and a complimentary clinical skill set to service members and interdisciplinary teams. This perspectives article explores the S/R dimension of MI, discusses the role of MHCs in CAF Mental Health (MH) Clinics, and provides clinical perspectives of an MHC regarding the treatment of MI. Key focuses of MHC interventions include bridging to other mental health services and supports, facilitating S/R coping and grounding, reconciling worldviews, resolving anger at a God-figure (not specific to any S/R perspective) and fostering reconciliation. Based on the literature, mental health practitioner’s feedback, and clinical experience, MHCs are integral to healing MI and warrant more widespread inclusion on interdisciplinary teams in CAF MH Clinics.